Gretimų garsų įtaka balsių kiekybei pietinių vakarų aukštaičių tarmėje - Kazlauskienė, Asta (Kalbotyra, 2000)
The paper analyses the dependence of the vowel length upon the voiced consonants and the adjacent syllable length in the south-western Aukštaitian dialect. The results of the research show that the word-middle vowels are the shortest before the voiceless consonants, longer before the voiced consonants - and the longest before the sonorants. The voiced consonant - in post-position, but not in pre-position, influences the length of a word-middle vowel: the vowel is longer when it is preceded by the voiceless consonant rather than voiced or vocal. The length of the word-end vowel, however, depends on the preceding voiced consonant: the word-end vowels are shorter when preceded by voiceless consonants or sonorants. The length of the adjacent syllable was not observed to have any influence on the stressed stem or word-end vowel duration. Unstressed word-middle vowels are shorter if they are followed by a long ending. The experiment demonstrated that there is a tendency to pronounce unstressed word-end vowels shorter if they are preceded by a long stressed syllable rather than a short one.